Brazilian copaifera species: Antifungal activity against clinically relevant candida species, cellular target, and in vivo toxicity - Andrade, Géssica; Orlando, Haniel Chadwick Silva; Scorzoni, Liliana [UNESP]; Pedroso, Reginaldo Santos; Abrão, Fariza; Carvalho, Marco Túlio Menezes; Veneziani, Rodrigo Cassio Sola; Ambrósio, Sérgio Ricardo; Bastos, Jairo Kenupp; Mendes-Giannini, Maria José Soares [UNESP]; Martins, Carlos Henrique Gomes; Pires, Regina Helena (MDPI, 2020)
Plants belonging to the genus Copaifera are widely used in Brazil due to their antimicrobial properties, among others. The re-emergence of classic fungal diseases as a consequence of antifungal resistance to available drugs has stimulated the search for plant-based compounds with antifungal activity, especially against Candida. The Candida-infected Caenorhabditis elegans model was used to evaluate the in vitro antifungal potential of Copaifera leaf extracts and trunk oleoresins against Candida species. The Copaifera leaf extracts exhibited good antifungal activity against all Candida species, with MIC values ranging from 5.86 to 93.75 µg/mL. Both the Copaifera paupera and Copaifera reticulata leaf extracts at 46.87 µg/mL inhibited Candida glabrata biofilm formation and showed no toxicity to C. elegans. The survival of C. glabrata-infected nematodes increased at all the tested extract concentrations. Exposure to Copaifera leaf extracts markedly increased C. glabrata cell vacuolization and cell membrane damage. Therefore, Copaifera leaf extracts are potential candidates for the development of new and safe antifungal agents.
Keywords: Antifungal; C. elegans–Candida infected model; Candida; Copaifera